The musical basis the story «Aboye the sea» by Lesya Ukrainka (Literatures of the World: Poetics, Mentality and Spirituality, 2020)
The article, using the intermedial approach, explores the features of the artistic reproduction of music in the story «Above the Sea» by the Ukrainian writer Lesya Ukrainka. It analyzes the role of songs, music of orchestras, sounds of the sea, etc. in the formation the musical palette of the work. The sea plays the key role in the story acoustic design, characterizes the heroes, creates a moody palette of the work, and psychologizes important plot-creating episodes.Lesya Ukrainka's using music in the story «Above the Sea» is interpreted as the need to optimize poetic potentials of prose, to update and modernize the genre of the story, to discover its unexplored possibilities, to intellectualize prose, to diversify and improve the artistic techniques and means of depicting the complex inner world of characters. The sea is a functional component of the musical palette of Lesya Ukrainka’s story. It is organically connected with the problematic, the plot of the work, has its own «history of relations» with the main character; it is a self-contained landscape component that keeps the mood balance of the work, the complex of experiences and actions of the storyteller. In the work music and the sea are in close contact, form a continuous and at the same time non-uniform emotional line, which describing the characters. According to modernist practice, Lesya Ukrainka represents the main character like a sensitive, vulnerable, emotional, and one, who perceives perfect sounds and unsurpassed colors of the sea as harmony.Panoramic visual and acoustic descriptions of the water element in Lesya Ukrainka’s story, as well as her numerous letters give us a reason to talk about the sea as an energy channel, a source of emotional and bodily recovery of the heroine and the author, a kind of axis, keeps the semantic structure of the work. The energy and the sounds of the sea artfully express the idea of the protection of heroine, who is aware of the value and fullness of life. Based on Lesya Ukrainka's letters, it is reasonable to interpret the therapeutic role of sea sounds and colors.
Keywords: music; sounds; rhythm; stories; intermedialism; existential issues; storyteller